Types of poetry figures (shabdalankar) of Mira Bai's poetry - ДОВБНЯ, К. (Київський національний університет імені Тараса Шевченка, 2020)
This article addresses the issue of the types of poetic figures (shabdalankar) in the poetry of the famous poetess of the medieval socio-religious movement bhakti Mira Bai, namely, an important category of Hindi poetry – alankars, which help to express aesthetic emotion – racu. Therefore, their study is of great importance for characterizing the work of Mira Bai in general. Alankars are usually called rhetorical figures, and their close translation – "decorations" – corresponds to the most important European rhetorical category fully, which covers the concept of figures and paths ornatus. They adorn the sound and meaning of the word and help to show aesthetic emotion – racu. It was suggested to study the types of shabdalankar (form decorations) in the poetry of Mira Bai. It was reviewed such shabdalankars as anupras (alliteration), yamaka (lexical repetition – "consonance"), vacrocti and shlesha (some types of paronomasia – "combination"). It was found that in the verses of Mira Bai there are mainly two of them – anupras and vipsa. A feature of the formal side of Mira Bai's works is miserly use of poetry adornments, since the poetry's verses are a cry of the soul, they reflect the unbearable pain of separation from her beloved Krishna. In such a state of mind, Mira Bai was not up to artificial decoration and play on words. If individual alancars appear in her poetry, it happens completely at ease. Only one of several shabdalankar dominates in the verses of Mira Bai, namely: anuprasa, which helps the poetess through the melody of the verse to create the mood she needs and clearly show the aesthetic emotion of love – the shringar's racu.

Розглянуто питання про види поетичних фігур (шабдаланкар) у поезії відомої поетеси середньовічного соціально-релігійного руху бгакті Міри Баї, а саме, важливу категорію поетики гінді – аланкари, які допомагають проявити естетичну емоцію – расу. Тому їх дослідження має неабияке значення для характеристики творчості Міри Баї загалом. Аланкари зазвичай називають риторичними фігурами, та й точний переклад їхньої назви – "прикраси" – повністю відповідає найважливішій європейській риторичній категорії, що охоплює поняття фігур і тропів ornatus. Вони прикрашають звучання й зміст слова і в такий спосіб допомагають проявити естетичну емоцію – расу. Запропоновано дослідження видів шабдаланкар (прикрас форми) в поезії Міри Баї. Розглянуто такі шабдаланкари, як анупраса (алітерація), ямака (лексичний повтор – "співзвуччя"), вакрокті й шлеша (деякі види парономасії – "поєднання"). Виявлено, що у віршах Міри Баї трапляються переважно дві з них – анупраса та віпса. Особливістю формальної риси творів Міри Баї є скупе використання нею прикрас поезії, оскільки вірші поетеси є криком душі, то в них відображено нестерпний біль від розлуки з коханим Крішною. У такому душевному стані Мірі Баї було не до штучного прикрашання й гри словами. Якщо й з'являються окремі аланкари в її поезії, то це відбувається абсолютно невимушено. У віршах Міри Баї домінує лише одна з кількох шабдаланкар, а саме: анупраса, яка допомагає поетесі через мелодику вірша створити потрібний їй настрій та яскраво проявити естетичну емоцію кохання – расу шрінгар.
Види поетичних фігур (шабдаланкар) у поезії Міри Баї
Keywords: аланкара; анупраса; віпса; шлеша; ямака; поетика гінді; alancara; anuprasa; vipsa; shlesha; yamaka; Hindi poetry